Evaluation of a steroid delivery system to mitigate the severity of proliferative vitreoretinopathy in a minipig model - Wong, Chee Wai; Cheung, Ning; Howden, James S.; Busoy, Joanna Marie Fianza; Sim, Shaun; Lim, Joshua; Ho, Candice; Veluchamy, Amutha Barathi; Storm, Gert; Wong, Tina T. (Frontiers in Ophthalmology, 2023)
Purpose To investigate the efficacy of liposomal prednisolone phosphate to mitigate the severity of proliferative vitreoretinopathy (PVR) in a minipig model of PVR. Methods A total of 18 eyes of 9 minipigs underwent PVR induction surgically. Eyes were randomized equally into three groups: intravitreal injection of liposomal prednisolone phosphate (LPP), triamcinolone acetonide (TA), and controls. PVR severity was graded on fundoscopic examination using a modified version of the Silicon Study Classification System. Severe PVR was defined as grade 2-5 on this classification, and the proportion of eyes with retinal detachment from severe PVR, defined as retinal re-detachment, i.e., PVR grade 2-5, was compared between treatment and control groups. Results On day 28, five eyes (83.3%) in the control group were observed to have severe PVR. Within the LPP group, one (16.7%) eye developed retinal detachment due to severe PVR. Grade 0 PVR was observed in four (66.7%) eyes, grade 1 in one (16.7%) eye, and grade 5 in one (16.7%) eye. Within the TA group, grade 0 PVR was observed in four eyes (66.7%), grade 1 in two eyes (16.6%), and grade 5 in one (16.7%) eye. The difference in the proportion of eyes with severe PVR was significantly lower in the LPP group compared to controls at day 28 (16.7% vs 83.3%, p=0.02). There was no significant difference in the rate of severe PVR or median PVR grade between the liposomal prednisolone phosphate and triamcinolone acetonide groups. Conclusion Liposomal prednisolone phosphate reduces the severity of PVR in a minipig model of PVR.